2007
DOI: 10.1001/archinte.167.20.2201
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Decision Aid to Assist Physicians in Reducing Unnecessary Antibiotic Drug Use for Acute Cystitis

Abstract: Background: In a previous study, use of a decision aid based on 4 clinical items would have reduced unnecessary antibiotic prescriptions for acute cystitis by 30% compared with usual physician care. Methods:We assessed the decision aid in a different population of females seen in community-based practice. Between April 7, 2002, and March 20, 2003, 225 Canadian family physicians recorded clinical findings, urine dip test results, and treatment decisions for 331 females with suspected cystitis. The number of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
2
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 20 publications
3
49
2
5
Order By: Relevance
“…The combination of leukocyte esterase and urinary nitrite could be used as an accurate, robust indicator for positive bacteria cultures. For other measures, pyuria with WBCs >5 per hpf was 72.7% sensitive for culture positivity, which is also within the range of 69% to 90% sensitivity as previously reported [6,10]. We found that bacteriuria was 92.9% specific, within the range of 89% to 94% from prior studies [6].…”
Section: Discussionsupporting
confidence: 89%
“…The combination of leukocyte esterase and urinary nitrite could be used as an accurate, robust indicator for positive bacteria cultures. For other measures, pyuria with WBCs >5 per hpf was 72.7% sensitive for culture positivity, which is also within the range of 69% to 90% sensitivity as previously reported [6,10]. We found that bacteriuria was 92.9% specific, within the range of 89% to 94% from prior studies [6].…”
Section: Discussionsupporting
confidence: 89%
“…16,18 The validation study by McIsaac et al, which combined clinical information and dipstick results (two or more of dysuria, leucocytes, and nitrites) did not weight these variables, did not use dipstick haematuria, and demonstrated modest predictive values (LR +ve test = 1.73 and LR -ve test = 0.43). 16 This supports the present authors' previous findings that clinical information is unlikely to add greatly to the predictive value when all three predictive variables from dipsticks are used. 19 The study by Hummers-Pradier et al had similar limitations (it did not use dipstick haematuria, did not weight variables, and had no separate derivation and validation samples) and also found modest predictive values.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…9,11,14-18 they have either not assessed the independent value of dipstick results and symptoms (hence potentially over-complicating clinical decision rules); and/or not used the range of dipstick variables (most include nitrite and leucocyte but not blood); and/or failed to develop and then test algorithms in separate samples (McIsaac et al being the exception 16 ); and/or had low power. Only the most recent dipstick studies have used the recent more rigorous laboratory guidelines for diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For females suspected of UTI, clinical decisions based on a diagnostic algorithm have been compared with care as usual by McIsaac et al 15 In their algorithm, antimicrobial prescription was recommended when at least two of the following clinical findings were present in females suspected of having a UTI: symptoms for 1 day, dysuria, positive leukocyte or nitrite test. The number of prescriptions in the case of a negative culture result could be reduced by 40% if their algorithm was implemented.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%